GENERAL DIDACTIC FUNDAMENTALS OF TEACHING WOMEN'S HANDMADE WORKS IN PUBLIC SCHOOLS OF WESTERN UKRAINE AT THE BEGINNING OF THE XX CENTURY - O.M. Slavopas (Освітній вимір, 2009)
In the article the general didactic principles of teaching of womas handworks at folk school of Western Ukraine at the beginning of XX age are analysed. Attention is concentrated on general didactic principles of teaching and their realization on lessons of woman handworks.